2020
DOI: 10.1002/ppul.24787
|View full text |Cite
|
Sign up to set email alerts
|

Impaired lung function following e‐cigarette or vaping product use associated lung injury in the first cohort of hospitalized adolescents

Abstract: Background Beginning June 2019, Children's Wisconsin was the first hospital to identify a cohort of adolescent patients hospitalized with symptoms likely associated with e‐cigarette use. Our report adds to the growing literature describing the radiographic, gross and cytopathologic bronchoscopic findings, and short‐term lung function outcomes in this cohort of adolescents with e‐cigarette or vaping product use associated lung injury (EVALI). Methods We present 15 adolescents hospitalized from June to September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 18 publications
(22 reference statements)
2
31
0
1
Order By: Relevance
“…In comparing to previous reports characterizing the symptoms and clinical course of patients affected by EVALI, our patients experienced similar clinical resolution (4,5,15,16). A majority of patients affected by EVALI show significant improvement by clinical (4,5,15), radiologic (8) and spirometric assessment (17).…”
Section: Discussionsupporting
confidence: 75%
“…In comparing to previous reports characterizing the symptoms and clinical course of patients affected by EVALI, our patients experienced similar clinical resolution (4,5,15,16). A majority of patients affected by EVALI show significant improvement by clinical (4,5,15), radiologic (8) and spirometric assessment (17).…”
Section: Discussionsupporting
confidence: 75%
“…Influenza is one of the consistent causes of death attributed to viral pneumonias every year [14]. EVALI due to vaping has been recently recognized as a concern in young patients who use vaping 168 devices [1][2][3][4][5][6][7][8]. Our patient had a complex of influenza-related severe lung injury and rhabdomyolysis further complicated by vaping of a mixture of Vitamin-E and THC.…”
Section: Discussionmentioning
confidence: 97%
“…The use of vaping devices is especially prevalent in the age group of 11 to 34-year-olds [1]. While the mechanism of lung injury in patients who vape is under investigation at the state and federal levels, vitamin E acetate, a chemical used to dilute tetrahydrocannabinol (THC) oil in vape cartridges, has emerged as one of the likely causes of EVALI [3][4][5][6][7]. In January 2020, the FDA finalized a policy that will prioritize enforcement against certain e-cigarette flavors and manufacturers of products that are targeted to minors or have failed to take adequate measures to prevent minors' access [8].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and imaging follow-up will be critical to ensure resolution of the pathologic process. Case reports have suggested that there may be residual lung dysfunction, mainly diffusion abnormalities, present for at least up to 2 months after discharge [ 35 , 36 ]. However, follow-up studies must be conducted to determine whether these abnormalities persist long term.…”
Section: Prognosis and Long-term Consequencesmentioning
confidence: 99%